Mitochondrial DNA Release Contributes to Intestinal Ischemia/Reperfusion Injury - Liao, Shishi; Luo, Jie; Kadier, Tulanisa; Ding, Ke; Chen, Rong; Meng, Qingtao (Frontiers in Pharmacology, 2022)
Mitochondria release many damage-associated molecular patterns (DAMPs) when cells are damaged or stressed, with mitochondrial DNA (mtDNA) being. MtDNA activates innate immune responses and induces inflammation through the TLR-9, NLRP3 inflammasome, and cGAS-STING signaling pathways. Released inflammatory factors cause damage to intestinal barrier function. Many bacteria and endotoxins migrate to the circulatory system and lymphatic system, leading to systemic inflammatory response syndrome (SIRS) and even damaging the function of multiple organs throughout the body. This process may ultimately lead to multiple organ dysfunction syndrome (MODS). Recent studies have shown that various factors, such as the release of mtDNA and the massive infiltration of inflammatory factors, can cause intestinal ischemia/reperfusion (I/R) injury. This destroys intestinal barrier function, induces an inflammatory storm, leads to SIRS, increases the vulnerability of organs, and develops into MODS. Mitophagy eliminates dysfunctional mitochondria to maintain cellular homeostasis. This review discusses mtDNA release during the pathogenesis of intestinal I/R and summarizes methods for the prevention or treatment of intestinal I/R. We also discuss the effects of inflammation and increased intestinal barrier permeability on drugs.